Molecular Characterization of a Novel Lipase-Like Pathogen-Inducible Gene Family of Arabidopsis - Jakab, Gabor (The American Society for Plant Biologists, 2003)
In a differential screening between Arabidopsis plants pretreated with the resistance-inducer β-aminobutyric acid and untreated control plants, we have identified a gene encoding a novel lipase-like protein, PRLIP1. The abundance of PRLIP1 mRNAs in Arabidopsis leaves was up-regulated by application of β-aminobutyric acid, salicylic acid (SA), and ethylene as well as by various pathogens. Induction of PRLIP1 depended on a functioning SA and ethylene signal transduction pathway but was independent of jasmonate signaling. This novel pathogenesis-related (PR) gene of Arabidopsis belongs to a gene family consisting of six (PRLIP1, PRLIP2, PRLIP4, PRLIP5, PRLIP6, and PRLIP7) closely related members in tandem position on chromosome 5. Among these genes, PRLIP2 also was induced in leaves by SA and infections by pathogens but on a much lower level than PRLIP1. The PRLIP1 family showed a tissue-specific expression pattern. Both PRLIP1 and PRLIP2 were specifically expressed in leaves and siliques, PRLIP1 additionally in stems and flowers. The expression of PRLIP6 and PRLIP4 was root specific, whereas mRNA of PRLIP5 and PRLIP7 were not detected in any of these tissues. The more distantly related genes PRLIP3, PRLIP9, and PRLIP8 were found on chromosomes 2, 4, and 5, respectively. The expression level of PRLIP3 was checked and found constitutive during the different stress conditions tested. The PRLIP1 gene was overexpressed in Escherichia coli, and the resulting PRLIP1 protein showed esterase activity on p-nitrophenyl-butyrate and allowed the growth of the bacteria on lipidic substrates such as Tween20 or Tween80.